Petroleum Chemicals (IntechOpen, 2023)
A vast amount has been written about petroleum fuels, including books and guidelines; hence, we thought it timely to produce a book Petroleum Fuels: Recent Updates, which covers the most important areas in the topic. In its pages, we tried to include advances toward green and sustainable viable products in terms of biodiesel production and chemical transformation. The book contains rich extracts from experts in the fuel field, including technical/environmental and econometric aspects.